Comparison Between Single Dose Versus Multiple Doses Antibiotics in Laparoscopic Cholecystectomy - Yadav, Umesh Kumar; Raya, Akash; Bhatta, Pashupati Nath; Rai, Binod Kumar; Yadav, Aditya Prakash; Shahi, Sanjiv Kumar (Med Phoenix, 2022)
Introduction Laparoscopic cholecystectomy is clean-contaminated surgery. Prophylactic antibiotics are used to reduce SSI but there is still controversy regarding use of antibiotics in postoperative period. The aim of this study is to compare the effect of single dose versus multiple doses of antibiotics in terms of wound infection. Methods This prospective study was carried out in department of surgery of National Medical College and Teaching Hospital, Birgunj from March 2020 to March 2021. Patients with diagnosis of symptomatic cholelithiasis were divided using lottery method in single dose (SD) group and multiple doses (MD) group. SD group were given injection ceftriaxone 1gm at the time of induction of anaesthesia and MD group received injection ceftriaxone 1gm at the time induction of anaesthesia and followed by continuation of same dose twice a day for 2 days. Results A total of 249 patients completed the study among which 127 patients were included in the (SD) group and 122 patients in (MD) group. The mean age of patient was 37.37±14.30 years. In single dose (SD) group, 4(3.1%) patients developed wound infection and 3(2.5%) patients in multiple (MD) group developed wound infection which was not statistically significant (p=0.437). Conclusions Single dose antibiotic was found to be as effective as multiple doses of antibiotics in terms of wound infection in laparoscopic cholecystectomy.